2012
DOI: 10.1007/s12639-012-0148-6
|View full text |Cite
|
Sign up to set email alerts
|

Egg laying strategies and effect of temperature on egg development of Argulus siamensis

Abstract: Argulus siamensis is the most damaging fish parasite prevalent in the freshwater aquaculture systems of India. In an attempt to further understand the behavior of this economically important parasite, the means of biological transmission, egg laying strategies and effect of temperature on development of eggs was studied. A. siamensis showed opportunistic egg laying behavior where in it used both living and non-living substrata for egg laying. It was marked that the parasites used the shells of freshwater snail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 17 publications
0
16
0
1
Order By: Relevance
“…According to Shafir and Oldewage (1992), peaks in the population of A. japonicus corresponded with reduced water levels as well as high temperatures. Sahoo et al (2013a) found optimum temperature of 28°C for the development of the eggs of A. siamensis into the infective metanaupliar stage. Mallik et al (2010) recorded the highest prevalence (70.1 %) in September and the lowest in December for S. richardsonii and T. putitora in Bhimtal lake while investigating the occurrence of Argulus spp.…”
Section: Risk Factors Associated With Argulosismentioning
confidence: 91%
See 1 more Smart Citation
“…According to Shafir and Oldewage (1992), peaks in the population of A. japonicus corresponded with reduced water levels as well as high temperatures. Sahoo et al (2013a) found optimum temperature of 28°C for the development of the eggs of A. siamensis into the infective metanaupliar stage. Mallik et al (2010) recorded the highest prevalence (70.1 %) in September and the lowest in December for S. richardsonii and T. putitora in Bhimtal lake while investigating the occurrence of Argulus spp.…”
Section: Risk Factors Associated With Argulosismentioning
confidence: 91%
“…Hakalahti et al (2004a, b) found that A. coregoni preferred to lay eggs on hard, dark colored and irregular substrates, preferably in deepwater or in the region covered with shadow. Sahoo et al (2013a) observed that A. siamensis showed opportunistic behavior with regard to egg laying wherein it used both, living and nonliving substrata for the purpose. It used the shells of freshwater snails, the runners of the water weeds and dead fish for laying eggs (Table 2).…”
Section: Risk Factors Associated With Argulosismentioning
confidence: 99%
“…A population of A. siamensis was maintained on stock rohu (approximately 500 g) in glass aquaria. The eggs deposited on the sides and bottom of the aquaria were collected in beakers containing tap water and incubated at 28°C with daily refreshment of water for hatching in a previously standardized way (Sahoo et al., ). After hatching, the metanauplii were counted and maintained in a tank for development to adult parasite on host rohu.…”
Section: Methodsmentioning
confidence: 99%
“…A population of A. siamensis was maintained on stock rohu (approximately 500 g) in glass aquaria. The eggs deposited on the sides and bottom of the aquaria were collected in beakers containing tap water and incubated at 28°C with daily refreshment of water for hatching in a previously standardized way (Sahoo, Mohanty, Hemaprasanth, Kar, Mohanty, Garnayak & Jena ). Upon hatching, the metanauplii were counted and maintained in similar conditions as the eggs till used in challenge test.…”
Section: Methodsmentioning
confidence: 99%